2016
DOI: 10.1097/dad.0000000000000452
|View full text |Cite
|
Sign up to set email alerts
|

Novel Use of Preoperative Epidermal Coloring of Very Small Dermatological Specimens—Protocol for Reduction of Lost Specimens

Abstract: Small tissue biopsies are often difficult to visualize and can be easily lost or mishandled. The authors hypothesized that full epidermal surface coloration of small skin lesions with a sterile skin marker (gentian violet ink) before performing shave biopsy would make small gross specimens easier to identify without impacting microscopic appearance. Live evaluation of 4 inked and 4 noninked gross (2-3 mm) specimens in covered and uncovered formalin-containing jars by 50 consecutive health care personnel demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The bone cutting lines on the bone surface, STA, and MCA were drawn using BV4 and gentian violet ink (►Figs. [2][3][4][5]. The colors of the BV4 and gentian violet inks were similar.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bone cutting lines on the bone surface, STA, and MCA were drawn using BV4 and gentian violet ink (►Figs. [2][3][4][5]. The colors of the BV4 and gentian violet inks were similar.…”
Section: Resultsmentioning
confidence: 99%
“…Methylrosaniline chloride (gentian violet or crystal violet) is used as a disinfectant, colorant, and active ingredients or additive in the manufacture of ethical drugs and cosmetics. 2,3) However, in 2014, the Food and Agriculture Organization of the United Nations/Food and Agriculture Organization of the United Nations issued a report on the substance. The World Health Organization Joint Expert Committee on Food Additives evaluated the genotoxicity and carcinogenicity of food additives and decided that an acceptable daily intake (ADI) could not be established for methylrosaniline chloride.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The application of Gentian violet ink to the patient prior to biopsy found that inked small specimens were significantly easier to visualize than non-inked small specimens without interfering with histopathologic analysis. 8 Root cause analysis was performed for several of the missing specimen incidents. This resulted in a policy at the academic institution to check the bottle for a specimen before leaving the room and initiation of a "specimen communication form" at the private dermatopathology laboratory which documents the details of each empty specimen bottle, for example, if two specimens were found in another bottle and require the lab director to sign off and clinician to be called and informed of the event.…”
Section: Discussionmentioning
confidence: 99%